Morphological and molecular identification for two new wood-inhabiting species of Botryobasidium (Basidiomycota) from China - Xin Li; Xin Zhang; Yi-Fei Sun; Zhen-Hao Li; An-Hong Zhu; Ying-Da Wu (MycoKeys)
The wood-inhabiting fungi refer to large basidiomycetes that grow on various woody materials and are distributed in various forest ecosystems, some of which have important economic value. In the present study, two new resupinate, adnate, wood-inhabiting fungal taxa, Botryobasidium latihyphum and B. zhejiangensis, are introduced based on morphological and molecular characteristics. A molecular phylogenetic study based on sequence data from the internal transcribed spacers (ITS) and the large subunit (nLSU) regions supported the two new species in the genus Botryobasidium. Maximum likelihood (ML), maximum parsimony (MP), and Bayesian inference (BIBI) were employed to perform phylogenetic analyses of these datasets. The new species B. latihyphum is characterized by its cream hymenial surface when fresh, olivaceous buff when dry, a monomitic hyphal system with clamp connections, the presence of clavate to tubular cystidia, basidia with six sterigmata, and broadly oval basidiospores measuring 7.9–10.2 × 3.2–4.3 μm. Botryobasidium zhejiangensis sp. nov. is characterized by its white to buff-yellow hymenial surface when fresh, cream when dry, a monomitic hyphal system with clamp connections, lacking cystidia, basidia with six sterigmata, and broadly navicular basidiospores measuring 7.9–9.2 × 2.6–3.4 μm. The phylogenetic result inferred from ITS + nLSU sequence data revealed that B. latihyphum is closely related to B. vagum, B. laeve, B. subincanum, and B. incanum, while B. zhejiangensis is closely related to B. leptocystidiatum, B. subcoronatum, B. xizangense, and B. intertextum.